Analisa Perbandingan Rencana Mutu Kontrak (RMK) Antara Penyedia Jasa Dengan Standar Pekerjaan Umum - Sari, Kharisma Permata; Chairi, Maiyozzi; Desfita, Mediana; Faismon4, Riki Hendra (JURNAL RIVET, 2024)
One way that contractors or service providers do to provide satisfaction to customers or service users, by improving the quality of the services offered. One of the applications is to compare the Contract Quality Plan (RMK) Document implemented by contractors or service providers for the Solok City Hospital Development Advanced Project and the Marahadin Laing Football Field Construction Advanced Project. This research method is quantitative with a comparative method that compares two or more of a variable, situation, event, activity or in the form of similarities and differences in planning and implementation. Based on the evaluation of the completeness of the contents of the Contract Quality Plan (RMK) document, the total percent obtained from the evaluation of the completeness of the contents of the Contract Quality Plan Document (RMK) obtained from the Solok City Hospital Construction Continuation Project was 61.90% and the Marahadin Laing Football Field Construction Continuation Project was 54.76%. This assessment is carried out based on the completeness of the contents of the Contract Quality Plan Document which refers to the Contract Quality Plan Document (RMK) which regulates in the Regulation of the Minister of General Employment Number: 04/PRT/M/2009.